2000
DOI: 10.1161/01.str.31.10.2287
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin C Concentration Was Inversely Associated With Subsequent 20-Year Incidence of Stroke in a Japanese Rural Community

Abstract: Background and Purpose-Epidemiological evidence suggests that vitamin C may decrease the risk of stroke. The purpose of the present study was to examine the association of serum vitamin C concentration with the subsequent incidence of stroke. Methods-In a Japanese rural community, a cohort of 880 men and 1241 women aged 40 years and older who were initially free of stroke was examined in 1977 and followed until 1997. The baseline examination included a measurement of serum vitamin C concentration. The incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
3
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 45 publications
(36 reference statements)
7
88
3
1
Order By: Relevance
“…The authors concluded that vitamin C status was as strong a predictor of death from stroke as diastolic blood pressure (9) . An inverse correlation between vitamin C status and stroke was also reported from a study (2121 subjects) in a rural Japanese population aged 40 years or older (42) . In the 12-year follow up on the Basel Prospective Study, a significantly increased risk of IHD and stroke was found in individuals with plasma ascorbate , 22·7 mmol/l, corresponding to severe or marginal vitamin C deficiency (43 -45) .…”
Section: Marginal Vitamin C Deficiencysupporting
confidence: 59%
“…The authors concluded that vitamin C status was as strong a predictor of death from stroke as diastolic blood pressure (9) . An inverse correlation between vitamin C status and stroke was also reported from a study (2121 subjects) in a rural Japanese population aged 40 years or older (42) . In the 12-year follow up on the Basel Prospective Study, a significantly increased risk of IHD and stroke was found in individuals with plasma ascorbate , 22·7 mmol/l, corresponding to severe or marginal vitamin C deficiency (43 -45) .…”
Section: Marginal Vitamin C Deficiencysupporting
confidence: 59%
“…It has been shown that delayed use of r-tPA leads to hyperperfusion which results in the accumulation of free radicals and the up-regulation of matrix metalloproteinases (MMPs) including MMP-9 [6,7] and these events lead to more injuries to the brain parenchyma. Under normal conditions, the endogenous and exogenous antioxidants scavenge free radicals and inhibit the harmful effects of oxidative stress [8]. Previous investigations revealed that after IBI, the concentrations of glutathione and ascorbic acid (AA) are decreased, while free radicals are increased [9,10], suggesting that increasing the concentration of AA, which may act as an antioxidant under these conditions, could be considered as new therapeutic strategy for treatment of IBI [11].…”
mentioning
confidence: 99%
“…A protective effect of fruits, vegetables, and whole grain on stroke development has been reported [89][90][91][92]. Mechanisms proposed include the lowering of blood pressure associated with dietary fibre, reduction of serum cholesterol by dietary soluble fibre, increased potassium intake, antioxidant vitamin effects, and decreased homocysteine levels by provision of dietary folate [89,92].…”
Section: Vegetables Fruits Grains and Fibresmentioning
confidence: 99%
“…The Basel Prospective Study [98] and the recent Shibata Study [90] suggested that low vitamin levels are associated with stroke, but clinical trials…”
Section: Vitaminsmentioning
confidence: 99%